John Steinbeck playing tug-of-war - unknown:::Creator::::::::::::
John Steinbeck, wearing shirt and tie, plays tug-of-war on the occasion of a picnic-barbecue for the birthday of John Short, Senior, at Short's home. From left to right stand Henry Williams; Major Morgan; Henry Dickinson; unknown woman; John Short, Junior; John Steinbeck; Wilfred Davis.